FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL - Wulandari Desiana Lestari (Institut Citra Internasional, 2026)
Chronic Energy Deficiency (CED) is a condition of long-term nutritional deficiency characterized by an upper arm circumference (LiLA) of less than 23.5 cm, which increases the risk of pregnancy complications such as anemia, premature labor, and low birth weight. Based on data from the Health Office of the Bangka Belitung Islands Province in 2024. This study aims to determine the factors associated with the incidence of CED in pregnant women in the working area of the Mentok Health Center, West Bangka, in 2024. This is a quantitative study using a case-control design. The sample consisted of 78 respondents, with 39 pregnant women experiencing CED as the case group and 39 pregnant women without CED as the control group. Data were obtained from the maternal health register and analyzed using the Chi-square test.The results showed significant associations between: education (p-value = 0.004; OR = 4.762), age (p-value = 0.006; OR = 6.452), pregnancy spacing (p-value = 0.024; OR = 5.250), and parity (p-value=0.006; OR=6.452) with the incidence of CED in pregnant women. The conclusion of this study is that education, age, pregnancy spacing, and parity are significantly associated with the incidence of Chronic Energy Deficiency (CED) in pregnant women in the working area of the Mentok Health Center, West Bangka, in 2024.